SURVEY OF DENTAL STUDENTS’ ATTITUDE REGARDING ORIENTAL MEDICINE/COMPLEMENTARY AND ALTERNATIVE MEDICINE: COMPARISON BETWEEN TWO JAPANESE DENTAL SCHOOLS - Kameyama, Atsushi; Toda, Kazuo (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The present study aimed to examine the impact of “curricula for undergraduate education in orientalmedicine (OM)/complementary and alternative medicine (CAM)” on student awareness of OM. A questionnaire surveywas conducted involving the Nagasaki University School of Dentistry (NUSD), a university that implements educationin OM as part of its undergraduate curriculum, and Tokyo Dental College (TDC), which does not teach OM.Materials and methods: The third- and fifth-year students of both NUSD and TDC underwent the anonymousquestionnaire survey, which included questions regarding their knowledge of OM and CAM, interests in these subjects,and their opinions on the necessity of teaching OM in the undergraduate dental education, and the results werecollected for analysis.Results: Whereas 33% of 5th year NUSD students had knowledge of OM/CAM was 33%, only 10% of 5th year TDCstudents reported knowledge on the subject. 69% of 5th year NUSD students interested in OM/CAM, while 5th yearTDC students who interest them were only 45%. Although 77% of 5th year NUSD students were in favor of OMeducation implemented in the Faculty of Dentistry, the percentages of TDC students of that were smaller (46% in 3rdyear and 48% in 5th year). Whereas 26% of 5th year TDC students did not recognize the necessity of oriental medicineeducation, only one 5th year NUSD student (2%) did not so.Conclusion: Introduction of education in OM in the undergraduate dental education program helps students to increasetheir interests in dental clinical applications.